OsTGAP1, a bZIP Transcription Factor, Coordinately Regulates the Inductive Production of Diterpenoid Phytoalexins in Rice - Okada, Atsushi (American Society for Biochemistry and Molecular Biology, 2009)
Production of major diterpenoid phytoalexins, momilactones and phytocassanes, is induced in rice upon recognition of pathogenic invasion as plant defense-related compounds. We recently showed that biosynthetic genes for momilactones are clustered on rice chromosome 4 and co-expressed after elicitation, mimicking pathogen attack. Because genes for most metabolic pathways in plants are not organized in gene clusters, examination of the mechanism(s) regulating the expression of such clustered genes is needed. Here, we report a chitin oligosaccharide elicitor-inducible basic leucine zipper transcription factor, OsTGAP1, which is essential for momilactone biosynthesis and regulates the expression of the five genes in the cluster. The knock-out mutant for OsTGAP1 had almost no expression of the five clustered genes (OsCPS4, OsKSL4, CYP99A2, CYP99A3, and OsMAS) or production of momilactones upon elicitor treatment. Inductive expression of OsKSL7 for phytocassane biosynthesis was also largely affected in the ostgap1 mutant, although phytocassane accumulation still occurred. Conversely, OsTGAP1-overexpressing lines exhibited enhanced expression of the clustered genes and hyperaccumulation of momilactones in response to the elicitor. Furthermore, enhanced expression of OsKSL7 and hyperaccumulation of phytocassanes was also observed. We also found that OsTGAP1 overexpression can influence transcriptional up-regulation of OsDXS3 in the methylerythritol phosphate pathway, eventually leading to inductive production of diterpenoid phytoalexins. These results indicate that OsTGAP1 functions as a key regulator of the coordinated transcription of genes involved in inductive diterpenoid phytoalexin production in rice and mainly exerts an essential role on expression of the clustered genes for momilactone biosynthesis.